TECTONO-SEDIMENTARY EVOLUTION OF THE EOCENE TRANSGRESSIVE DEPOSITS IN THE ACIGÖL, BURDUR AND ISPARTA AREAS (SW TURKEY) - EZHER TOKER; FUZULI YAĞMURLU (Acta Geographica Debrecina. Landscape & Environment Series)
The Eocene transgressive deposits of the Acıgöl, Burdur and Isparta basins are the best exposed of the SW Turkey and shed light on one of the outstanding problems of the tectono-sedimentary evolution during paleotectonic and neotectonic period. In the present paper we describe a tectonic model of the progressive foreland migration of the allochthonous units such as Lycian and Antalya nappes, initialemplacement onto stable carbonate platform in the Early Oligocene, carrying piggy-back basins and incorporating from alluvial fan to deep-marine deposits recognized in these terrigenous successions.In general, the facies and structural observations on the overall Mid-Late Eocene clastic sequences, outcropping in behind the Lycian nappes, indicate: i) the alluvial fan to shallow marine settings of the Başçeşme Fm in Acıgöl, ii) the Varsakyayla Fm in Burdur and iii) proximal to distal flysch facies trend of the Kayıköy Fm in Isparta. The collected data allow us to hypothesize that the Mid-Late Eocene tectono-sedimentary history was characterized by a terrigenous clastics, probably lying on the constructing tectonic edifice and then deformed and covered by a piggy-back like sequence. Thetectono-sedimentary evolution of the Eocene transgressive in SW Turkey has been probably developed through a progressive migration towards the foreland basin.